Pelaksanaan kebenaran merancang di kawasan luar bandar kajian kes : Pihak Berkuasa Tempatan Utara Negeri Selangor - Yahya, Nina Izurin (2010)
Act 172 or The Town and Country Planning Act 1976 was designed specially to cater the need pertaining to development control and to have uniformity on physical development in all urban and rural area. However, Development activities related to town and country planning in this country are not only bounded by the Town and Country Planning Act 1976(Act 172) but also other existing legislations such as the National Land Code 1965 (Act 56), Street, Drainage and Building Act 1974 (Act 133), Uniform Building By-Laws 1984 and a few others. Although all the act indirectly empowers the State Authority to create policies with regards to development and land use policies within the state, the real power lies within the hand of the Local Authority. The Local Authority in enforcing planning control is also guided by other mechanisms such as rules and regulations, standards and guidelines. Therefore the main aim of the paper is to explain the mechanisms for planning control especially from the perspective of current legislations. It focuses on the mechanisms, processes and procedures that are provided in the Town and Country Planning Act 1976 (Act 172), Planning Control (General) Rules and National Land Code 1965 (Act 56), that can assist local authorities in practicing planning control. The emphasis is given to Planning Permission Procedures with regards to the rural area. This is important as it has become trend among local authorities to disregards planning permission procedures for development within the agriculture land. Besides gathering data from related portal, documents and article, it will involve interviews between selected agencies, consultant and the decision maker level. Based on the interviews and findings, the study will come up with several proposal such as introducing to new procedures and implementation mechanism such as conducting further studies on related issues for the reference of State and Local Authorities.